Етичні проблеми адаптивного спорту (на прикладі Паралімпійських ігор) - Захаріна, Євгенія Анатоліївна; Zakharina, Eugene (Східноєвропейський національний університет імені Лесі Українки, 2015)
Незважаючи на значний позитивний ефект олімпійських ідеалів, традицій, принципів і цінностей, на жаль, в адаптивному спорті спостерігають прояв і негативних тенденцій сучасного олімпійського руху. Завдання дослідження – проаналізувати та визначити етичні проблеми сучасного адаптивного спорту на прикладі Паралімпійських ігор. Розвиток паралімпійського спорту як складової частини адаптивного спорту, з одного боку, свідчить про реалізацію в ньому фундаментальних ідей олімпізму, з іншого – про неодноразове їх недотримання й порушення. Важливим аспектом, що сприяє розвитку паралімпійського спорту, має стати зміна ціннісних пріоритетів – від прагнення до досягнення найвищих результатів до ідеї максимальної інтеграції осіб з інвалідністю до умов життєдіяльності здорових за допомогою занять спортом. Despite the significant positive impact of the Olympic ideals, traditions, principles and values, unfortunately, adaptive sports still have some negative trends of the modern Olympic movement. To analyze and to identify the cause of the ethical problems in Paralympic sport.the ethical problems of modern adaptive sports in Paralympic Games for example. On the one hand, development of Paralympic sport as an integral part of adaptive sports evidences implementation of the fundamental ideas of olympism in it. On the other hand –it proves non-compliance and the frequent violation of these ideas. An important aspect of promoting the development of Paralympic sport, should be a change of value priorities – from the desire to achieve the best results to the idea of maximum integration of people with disabilities to the conditions of life of people without disabilities through sports. Key words: adaptive sport, Paralympic Games, athletes with disabilities, ethical problems. Despite the significant positive impact of the Olympic ideals, traditions, principles and values, unfortunately, adaptive sports still have some negative trends of the modern Olympic movement. To analyze and to identify the cause of the ethical problems in Paralympic sport.the ethical problems of modern adaptive sports in Paralympic Games for example. On the one hand, development of Paralympic sport as an integral part of adaptive sports evidences implementation of the fundamental ideas of olympism in it. On the other hand –it proves non-compliance and the frequent violation of these ideas. An important aspect of promoting the development of Paralympic sport, should be a change of value priorities – from the desire to achieve the best results to the idea of maximum integration of people with disabilities to the conditions of life of people without disabilities through sports.
Ethical Problems of Adaptive Sports (for Example, in Paralympic Games)
Keywords: адаптивний спорт; Паралімпійські ігри; спортсмени з інвалідністю; етичні проблеми; adaptive sport; Paralympic Games; athletes with disabilities; ethical problems